Knowledge management and e-learning - Frank, Michael S.; Liebowitz, Jay , 1957- (Auerbach Publications, 2011)
Combines knowledge management (KM) with e-learning as complementary approaches. This book looks at KM practices in e-learning and covers various techniques and methodologies. It explains knowledge capture, retention, transfer, and sharing. It contains case studies looking at applications of KM to e-learning in businesses, and universities